Penerapan Pembelajaran Autonomi dalam Meningkatan Keterampilan Membaca Text Bahasa Inggris - Mardiyah, Mutmainatul (LPPM Universitas Mohammad Husni Thamrin, 2018)
To describe how autonomous learning increases students’ English text reading skills. The research was conducted at Faculty of Economics, MH. Thamrin University, East Jakarta. The result of the research is as follows: (1) autonomous learning implementation at Faculty of Economics, MH. Thamrin University is generally good. The achievement of all indicators of autonomous learning is very high. (2) Students’ English text reading skills at Faculty of Economics, MH. Thamrin University is generally very good. The achievement of all indicators of reading skills strategies is very high. (3) Autonomous learning has been successfully implemented to increase the students’ English text reading skills at Faculty of Economics, MH. Thamrin University. Based on the research result, the students’ English text reading skills could be enhanced by deeply implementing the indicators of autonomous learning through 1). Developing self-awareness, 2). Developing effective learning strategies, 3). Developing thinking skills, 4). Developing organizational skills, 5). Developing cooperative skills, 6). Developing metacognitive skills, 7). Developing problem solving dan supporting others. It proves that autonomous learning can increase students’ English text reading skills.